Thiophene compound, modified positive electrode material, preparation method of modified positive electrode material and lithium ion battery
Modifying the oxide solid electrolyte by thiophene compounds solves the problems of cycle life attenuation and safety risks of lithium-ion batteries under high temperature and rate conditions, and achieves the improvement of the battery's high temperature cycle and rate performance.
Patent Information
- Application Number
- CN202411498179.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-24
AI Technical Summary
Existing lithium-ion batteries show cycle life attenuation and safety risks under high temperature and magnification conditions, mainly due to the side reaction of the positive electrode material with the electrolyte and the oxidative conversion of solid electrolytes.
The oxide solid electrolyte is modified by grafting the functional groups of the thiophene group, and the residual base on the surface of the solid electrolyte is transformed and the metal-hydroxy active center is deactivated, thereby blocking the side reaction with the solvent.
It effectively improves the high-temperature cycling and rate performance of lithium-ion batteries, reduces the side reaction between the positive electrode material and the electrolyte, and improves the structural stability and safety performance of the battery.
Smart Images

Figure CN119431305A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a thiophene compound, a modified positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] As a key material of the battery, the positive electrode material is a key component that determines the battery voltage and energy density. At present, the mainstream positive electrode materials are mostly lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, etc. These materials have the common problem of producing side reactions with the electrolyte during the charging and discharging process, which leads to the degradation of the electrode material and causes a significant attenuation of the battery cycle life. At the same time, due to the free HF produced by the decomposition of lithium salts in most electrolytes, the transition metal ions on the surface of the positive electrode are easily corroded in the electrolyte, resulting in the decay of the electrode material and the decay of the battery capacity, which in turn triggers strong side reactions that cause the battery to thermally run away and explode.
[0003] At present, it is generally believed that the use of surface coating to isolate the electrode material from the electrolyte can reduce the side reactions of the two and effectively solve the above-mentioned series of problems. Studies have shown that surface coating, as a mainstream method for stabilizing the surface of positive electrode materials, can effectively inhibit the side reactions on the surface of the positive electrode. There are many coating methods in the prior art. For example, a Chinese patent document with publication number CN 108682819 A discloses a process for directly coating the positive electrode with a solid electrolyte, which mainly uses carbon materials and solid electrolyte materials to perform composite coating modification on the positive electrode material.
[0004] Although this method effectively introduces solid electrolyte materials as a coating layer and solves the rate and room temperature cycle performance, it is difficult to solve the high temperature performance. Summary of the invention
[0005] In view of this, the present invention provides a thiophene compound, a modified positive electrode material and a preparation method thereof, and a lithium ion battery. The modified positive electrode material provided by the present invention is a composite coated material, which is applied to lithium ion batteries to achieve a comprehensive improvement in high temperature cycle and rate performance.
[0006] In order to simultaneously solve the rate and high-temperature cycle problems of ternary lithium batteries, the present invention uses solid electrolyte composite coating to modify the surface of the positive electrode material.
[0007] Solid electrolyte materials have good structural stability and high ionic conductivity, which can effectively reduce the positive electrode interface impedance, accelerate the migration rate of lithium ions on the positive electrode surface, and thus effectively improve the battery's cycle and rate performance. However, most oxide solid electrolytes have a lot of residual alkali on the surface, which will cause gelation in the battery. At the same time, the metal-hydroxyl active center groups on the surface of the solid electrolyte are easily oxidized and transformed at high temperatures, and then react with the solvent to capture hydrogen atoms in the solvent molecules, thereby catalyzing the decomposition of the electrolyte, resulting in poor high-temperature cycle effects.
[0008] The present invention provides a thiophene compound having a structure of Formula I:
[0009]
[0010] Wherein, X1 and X2 are independently selected from halogen elements (halogen for short), including fluorine (F), chlorine (Cl), bromine (Br), etc., preferably bromine; X1 and X2 can be the same or different, preferably both are bromine. X1 and X2 are both in the meta position of the S atom, and the thiophene ring contains α-H, and the thiophene molecules can be polymerized. In addition, in formula I, (CH2) 1-2 It can represent one methylene group or two methylene groups (CH2CH2).
[0011] In a preferred embodiment of the present invention, the thiophene compound has a structure as shown in Structural Formula A, which can be referred to as Compound A for short;
[0012]
[0013] Further, the present invention takes the compound A as an example to illustrate its preparation method, but is not limited to the preparation method provided by the present invention:
[0014] First, aluminum chloride (AlCl3) is preferably used as a catalyst to catalyze the halogen substitution reaction of aldehyde-containing acrylthiophene to obtain an aldehyde-containing halogenated thiophene compound; the halogen substitution reaction is preferably a bromine substitution reaction, which can be carried out in a solvent such as dichloromethane (CH2Cl2), and the reaction temperature is preferably 0°C;
[0015] Then, preferably under the catalytic action of a mixed catalyst of titanium tetrachloride (TiCl4) and zinc powder (Zn powder), the aldehyde-containing halogenated thiophene compound is condensed to obtain compound A; the halogen element is bromine, the condensation temperature can be -20°C to -10°C, and the solvent involved includes but is not limited to tetrahydrofuran (THF). The specific reaction formula is as follows:
[0016]
[0017] The thiophene compound of the present invention has a general structure of formula I, and can effectively modify the oxide solid electrolyte, convert the residual alkali on its surface into a favorable component, and graft the functional group containing the thiophene group, so that the metal-hydroxyl active center on the surface can be completely inactivated. On the basis of taking into account the original performance of the oxide solid electrolyte, it can effectively block the reaction with the solvent and improve the high temperature cycle performance. And due to the elimination of the residual alkali on the surface, the phenomenon of gelation caused by excessive alkalinity during the homogenization process is effectively avoided.
[0018] In addition, the synthetic raw materials of the thiophene compound represented by formula I of the present invention are easily available in the market, have low cost, are highly cost-effective, and are easy to prepare.
[0019] The present invention provides a modified positive electrode material, which comprises, from the inside to the outside, a lithium-containing core, a solid electrolyte shell layer coated on the surface of the lithium-containing core, and a carbon-containing shell layer, wherein the carbon-containing shell layer is formed by carbonization after polymerization of a monomer, and the monomer is the thiophene compound described above.
[0020] The embodiment of the present invention aims to modify the solid electrolyte coating layer coated on the surface of the positive electrode material through the above-mentioned functional compound A with a thiophene structure, and the molecules of the compound A can be polymerized to form a polymer coating film, and finally the outermost polymer coating film is pyrolyzed for secondary coating, and finally a modified positive electrode composite (modified positive electrode material) with a core-shell-shell double-layer coating is prepared, that is, the problems of structural instability, poor rate performance, and poor high-temperature cycle performance of the positive electrode material are effectively improved through solid electrolyte composite coating.
[0021] Accordingly, the present invention provides a method for preparing a modified positive electrode material, comprising the following steps:
[0022] Providing a lithium-containing positive electrode material coated with a solid electrolyte shell layer;
[0023] The lithium-containing positive electrode material coated with the solid electrolyte shell layer is reacted with a functional compound, wherein the functional compound is the thiophene compound described above, so that the thiophene compound is grafted onto the surface of the solid electrolyte shell layer and polymerized into a coating film to obtain an intermediate;
[0024] The intermediate is subjected to pyrolysis treatment under a protective atmosphere to obtain a modified positive electrode material with a double-layer coating structure.
[0025] In the embodiment of the present invention, a lithium-containing positive electrode material coated with a solid electrolyte shell is first prepared, wherein the thickness of the solid electrolyte shell is preferably 200 to 400 nm, and can be 210 to 350 nm, etc. The preparation of the lithium-containing positive electrode material coated with a solid electrolyte shell comprises: dry mixing a lithium-containing positive electrode material raw material and a solid electrolyte, and then sintering at a high temperature to obtain the obtained material.
[0026] The raw materials of the lithium-containing cathode material described in the present invention correspondingly form a lithium-containing core structure at the innermost part of the material. Further, its composition is selected from one or more of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganate, lithium nickelate, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel manganate, and lithium-rich manganese oxide. Further still, the present invention preferably selects lithium nickel cobalt manganese oxide, etc.
[0027] In the embodiment of the present invention, the solid electrolyte and the raw materials of the lithium-containing cathode material are added to a high-speed mixer according to a ratio, and dry mixing is carried out for physical mixing, and then through high-temperature sintering, the first coating is completed to form a cathode precursor with a solid electrolyte shell layer. This step cleverly coats the solid electrolyte material uniformly on the surface of the cathode material to form a coating shell layer (that is, the solid electrolyte shell layer coated on the surface of the lithium-containing core), which can directly isolate the cathode material from the electrolyte, improve the conductivity, and enhance the rate performance at the same time. The preparation of the cathode precursor described in the embodiment of the present invention adopts a dry coating method, which not only effectively avoids the problems of complex interface between the cathode material and the electrolyte in wet coating and low process efficiency, but also has a simple process and is easy to industrialize.
[0028] Further, the composition of the solid electrolyte and the shell layer is a NASICON-type oxide solid electrolyte. The chemical formula of the NASICON-type oxide solid electrolyte is Li 1+x A x E 2-x (PO4)3; wherein, the A-site element is one or several of aluminum (Al), lanthanum (La), gallium (Ga), iron (Fe), scandium (Sc), lutetium (Lu), and yttrium (Y); the E-site element is one or several of titanium (Ti), germanium (Ge), zirconium (Zr), hafnium (Hf), and tin (Sn); where 0 ≤ x ≤ 0.5. The solid electrolyte is more preferably lithium aluminum titanium phosphate, with aluminum at the A-site and titanium at the E-site; the chemical formula is: Li 1+y Al y Ti 2-y P3O 12 , where 0.3 < y < 0.6, and it can be 0.35, 0.4, 0.45, or 0.5, etc., which is simply referred to as LATP.
[0029] Preferably, in the preparation process of the lithium-containing positive electrode material coated with the solid electrolyte shell layer, the mass ratio of the lithium-containing positive electrode material raw material to the solid electrolyte is (1-m):m, 0<m≤0.1. Further, the temperature of the high-temperature sintering is 0.2 to 0.5 times the melting point of the solid electrolyte, for example, the temperature of the high-temperature sintering is 90 to 300°C, and further 100 to 250°C. In an embodiment of the present invention, the above-mentioned positive electrode material raw material and the coating material can be added to a high-speed mixer according to a mass ratio of (1-m): m, 0<m≤0.1, and preferably mixed at a speed of 800-1000 rpm for 15-25 minutes to obtain a premix; then the premix is put into a fusion coating machine, the blade speed range can be 2000-4000 rpm, and the coating is carried out for 15-30 minutes under a protective environment such as nitrogen, and the coated positive electrode material is subjected to high-temperature treatment in the range of (0.2-0.5) Ta (Ta is the melting point of the coating material), thereby obtaining a positive electrode precursor coated with a solid electrolyte once, which is a lithium-containing positive electrode material coated with a solid electrolyte shell.
[0030] After preparing the lithium-containing positive electrode material coated with a solid electrolyte shell, the embodiment of the present invention reacts it with a functional compound (the thiophene compound described above) to graft the thiophene compound onto the surface of the solid electrolyte shell and polymerize into a coating film; the obtained intermediate is pyrolyzed under a protective atmosphere to obtain a modified positive electrode material with a double-layer coating structure.
[0031] The embodiment of the present invention provides a method for modifying a composite coated positive electrode material with a solid electrolyte, specifically comprising: reacting a synthesized functional compound A, etc. with the solid electrolyte on the surface of the above-mentioned positive electrode precursor to form a chemical connection bond, so that the compound A can be grafted onto the surface of the solid electrolyte, and at the same time, the functional group in the compound A is polymerizable, which can evenly form a layer of dense polymer coating film outside the solid electrolyte coating layer on the surface of the positive electrode particles, and finally the outermost polymer coating film is pyrolyzed to obtain a final product having a double-layer coated modified positive electrode composite with a core-shell-shell structure, which is the modified positive electrode material.
[0032] In some embodiments of the present invention, the reaction of the lithium-containing cathode material coated with a solid electrolyte shell and the functional compound is carried out under stirring in the presence of an alkaline solution; the molar ratio of the lithium-containing cathode material and the functional compound is (0.4-0.6):1, further 0.5:1; the alkaline solution is preferably a carbonate aqueous solution, and the molar concentration may be 0.1-0.2 mol / L. Further, the reaction temperature is 100-120°C, for example 105-115°C, and the reaction time may be 24-30h, specifically 24h of stirring reaction.
[0033] Specifically, compound A and a positive electrode precursor coated with 200-400nm thick LATP can be catalyzed by potassium carbonate (K2CO3) under a protective atmosphere such as nitrogen to react the hydroxyl -OH on the surface of the solid electrolyte with bromine to form an ether bond to obtain a surface grafted modified material. The reaction formula involved is as follows (R-Br is the abbreviation of compound A, and R contains a polymerizable thiophene structure). Continue stirring under alkaline conditions (sodium carbonate, potassium carbonate solution) to polymerize the surface grafted compound A molecules to form a dense polymer coating film, which is an intermediate with a core-shell structure;
[0034]
[0035] Finally, the intermediate with a core-shell structure is subjected to pyrolysis treatment under a protective environment such as nitrogen for 20 to 30 minutes. The pyrolysis temperature range is preferably 200 to 300°C, further 210 to 290°C. After cooling, a positive electrode composite with a core-shell-shell double-layer coating structure is obtained, which is a modified positive electrode material with a double-layer coating structure.
[0036] The positive electrode composite prepared by the embodiment of the present invention adopts a composite coating method, which can not only ensure the stability of the positive electrode material structure, but also directly isolate the positive electrode material and the electrolyte, effectively reducing the side reactions of the positive electrode and the electrolyte; at the same time, after the functional compound shown in the synthetic formula I modifies the solid electrolyte in the positive electrode precursor, the formed polymer coating layer is further pyrolyzed into a carbon-containing shell layer, which can not only improve the electronic conductivity while maintaining the original excellent properties, but also coordinate the inherent fast ion conductivity of the solid electrolyte, and can take into account the improvement of electronic conductivity and ion conductivity, thereby significantly alleviating the polarization phenomenon under rapid charge and discharge, and enhancing the rate performance of the battery. Furthermore, the residual alkali in the solid electrolyte is converted into a favorable component, which blocks the high-temperature side reaction of the solid electrolyte and the solvent from the source, inhibits the dissolution of transition metal elements, and thus improves the high-temperature cycle performance of the lithium battery.
[0037] The present invention provides a positive electrode sheet, wherein the modified positive electrode material described above or the modified positive electrode material obtained by the preparation method described above is used as an active material. Specifically, the positive electrode sheet comprises an active material, a conductive agent, a binder and a current collector, and the active material is the positive electrode composite described above.
[0038] Furthermore, the conductive agent is selected from one or more of carbon black, acetylene black, Ketjen black, graphene, and carbon nanotubes; the present invention gives priority to carbon black and carbon nanotubes.
[0039] Furthermore, the binder is selected from one or more of polyvinylidene fluoride, polyethylene oxide, and polyacrylic acid; polyvinylidene fluoride is preferred in the present invention.
[0040] Furthermore, the current collector is selected from one of aluminum foil, carbon-coated aluminum foil, and composite current collector; the present invention prefers carbon-coated aluminum foil.
[0041] Preferably, in the embodiment of the present invention, the active material, conductive agent and binder of the positive electrode are mixed in a mass ratio of 95-97:1-3:1-2, and the solid content is adjusted to 65-69% by adding N-methylpyrrolidone. After homogenization, coating, drying, rolling, slitting and die-cutting, a positive electrode sheet containing a positive electrode composite can be obtained.
[0042] The present invention provides a lithium ion battery, comprising the positive electrode sheet. The lithium ion battery is specifically a solid-liquid hybrid lithium ion battery, which includes a negative electrode, a separator and a non-aqueous electrolyte in addition to the positive electrode sheet containing the positive electrode composite.
[0043] Furthermore, the active material of the negative electrode is selected from any one of artificial graphite, natural graphite, lithium titanate, metallic lithium, silicon-carbon composite material and silicon monoxide. These materials are applied to the present invention alone or in combination, and artificial graphite is preferred in the present invention. The present invention has no special restrictions on the various materials of the negative electrode, and those commonly used in the art can be used.
[0044] Furthermore, the diaphragm is selected from polypropylene (PP) and polyethylene (PE) diaphragms; the present invention prefers PE diaphragms.
[0045] Furthermore, the non-aqueous electrolyte is a standard non-aqueous electrolyte comprising an organic solvent, a lithium salt and an additive. The solid-liquid hybrid lithium-ion battery has good compatibility between the positive and negative electrodes and the electrolyte.
[0046] Furthermore, the lithium salt is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalatoborate) (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiODFB) and lithium difluorobis(oxalatophosphate) (LiDODFP).
[0047] Further, the organic solvent is at least two of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, 1,4-butyrolactone, methyl formate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate and ethyl butyrate;
[0048] Furthermore, the additive is any one or more of vinylene carbonate, 1,3-propane sultone, fluoroethylene carbonate, vinyl sulfate or tris(trimethylsilyl)phosphate.
[0049] Furthermore, the mass fraction of the organic solvent in the non-aqueous electrolyte is 82.5-85.5%; the mass fraction of the lithium salt in the non-aqueous electrolyte is 12-14.5%; and the mass fraction of the additive in the non-aqueous electrolyte is 0.1-5.5%.
[0050] Some embodiments of the present invention can make button batteries in a glove box, stack the negative electrode, diaphragm, positive electrode sheet, stainless steel gasket, and spring in order, inject non-aqueous electrolyte, use a hydraulic crimping machine to seal, let stand, and obtain a solid-liquid hybrid battery sample after aging.
[0051] In summary, the embodiment of the present invention is to coat the solid electrolyte on the surface of the positive electrode material once by physically mixing the solid electrolyte and the positive electrode material and performing high-temperature sintering in two steps to form a positive electrode precursor; then the solid electrolyte is modified according to the synthesized functional compound, and the thiophene compound shown in Formula I is grafted onto the solid electrolyte on the surface of the positive electrode precursor. The polymerizable group in the thiophene compound can form a dense polymer conductive coating layer on the outermost layer of the solid electrolyte coating layer on the surface of the positive electrode material. Finally, the outermost polymer coating layer is used as a carbon source, and after heat treatment, a dense coating layer is formed on the outermost layer, thereby forming a modified positive electrode material (positive electrode composite) with a core-shell-shell double-layer coating structure. This positive electrode composite has a double-layer coating structure, has higher electronic conductivity and ionic conductivity, and can give the charge a rapid transmission capability between the interface and the bulk phase, while isolating the side reactions between the positive electrode material and the electrolyte, and the solid electrolyte and the solvent.
[0052] After testing, it was found that the solid-liquid hybrid lithium-ion battery prepared using a positive electrode composite can exhibit better electrochemical performance and better safety performance than conventional systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 is a SEM image of the positive electrode composite 1 in Example 1;
[0054] Figure 2 The capacity-voltage comparison curves of Example 1 and Comparative Example 1;
[0055] Figure 3 The figure is a comparison chart of the discharge performance at different rates of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0056] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in combination with the drawings and the like in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0057] In order to better illustrate the present invention, the following examples are further illustrated. Unless otherwise specified, the various reagents and raw materials used in the present invention are all commercially available products or products that can be prepared by recognized methods. Unless otherwise specified, the ratios involved are all mass ratios.
[0058] Regarding the preparation of compound A, the specific steps are as follows:
[0059]
[0060] Under nitrogen atmosphere, 2-formaldehyde-3-propenylthiophene (13.68 g, 0.09 mol) and 200 mL of ultra-dry dichloromethane were added to a 500 mL three-necked flask equipped with a magnetic rotor, and the reaction mixture was then transferred to a low temperature reactor and stirred, and cooled to 0°C. Subsequently, aluminum chloride (26.88 g, 0.20 mol) was gradually added to the solution in multiple portions, and the temperature of the reaction mixture was kept at 0°C. Subsequently, liquid bromine (5.00 mL, 0.1 mol) was added, and the mixture was continued to be stirred for reaction. After 3 h, the low temperature reactor was removed, and the mixed solution was poured into 300 mL of ice together with 100 mL of 1M hydrochloric acid aqueous solution and stirred for 30 min.
[0061] The organic layer was then separated, the solvent was removed under reduced pressure, and the residue was purified by silica gel chromatography with n-hexane as the eluent. After the solvent was removed by rotary evaporation, the intermediate brominated monomer 2-formaldehyde-3-propenyl-4-bromothiophene was obtained with a yield of 92.3%. GC-MS (m / z): calcd. for C8H7BrOS[M+1]+, 229.94, found 229.97.
[0062] Under nitrogen atmosphere, add 2-formaldehyde-3-propenyl-4-bromothiophene (11.50 g, 50.00 mmol) and 100 mL of ultra-dry tetrahydrofuran to a 250 mL three-necked flask equipped with a magnetic rotor, then transfer the flask to a low-temperature reactor and start stirring. When the system temperature drops to the preset temperature of -18 ° C, slowly add titanium tetrachloride (6.5 mL) and let stand for 30 minutes. After the addition is complete, continue stirring for 30 minutes, then add zinc powder (7.8 g) in small portions several times within 30 minutes. Continue to stir the mixture at -18 ° C for 1 hour, then remove the low-temperature reactor and continue to react at room temperature for 3 hours.
[0063] Finally, the reaction was quenched by adding 100 mL of ice water, the solid was filtered and collected, and the solid was dissolved in 80 mL of dichloromethane and filtered twice to remove insoluble inorganic matter. The filtrate was evaporated and the residue was recrystallized with n-hexane to obtain compound A with a yield of 94.7%. GC-MS (m / z): calcd.for C 16 H 14 Br2S2[M+1]+,427.89, found 427.92.
[0064] Compound B was prepared in the following specific steps:
[0065]
[0066] Under nitrogen atmosphere, 2-formaldehyde-3-butenylthiophene (14.94 g, 0.09 mol) and 200 mL of ultra-dry dichloromethane were added to a 500 mL three-necked flask equipped with a magnetic rotor, and the reaction mixture was then transferred to a low temperature reactor and stirred, and cooled to 0°C. Subsequently, aluminum chloride (26.88 g, 0.20 mol) was gradually added to the solution in multiple portions, and the temperature of the reaction mixture was kept at 0°C. Subsequently, liquid bromine (5.00 mL, 0.1 mol) was added, and the mixture was continued to be stirred for reaction. After 3 h, the low temperature reactor was removed, and the mixed solution was poured into 300 mL of ice together with 100 mL of 1M hydrochloric acid aqueous solution and stirred for 30 min.
[0067] The organic layer was then separated, the solvent was removed under reduced pressure, and the residue was purified by silica gel chromatography with n-hexane as the eluent. After the solvent was removed by rotary evaporation, the intermediate brominated monomer 2-formaldehyde-3-butenyl-4-bromothiophene was obtained with a yield of 90.9%. GC-MS (m / z): calcd. for C9H9BrOS, 243.96, found 243.86.
[0068] Under nitrogen atmosphere, add 2-formaldehyde-3-butenyl-4-bromothiophene (12.20 g, 50.00 mmol) and 100 mL of ultra-dry tetrahydrofuran to a 250 mL three-necked flask equipped with a magnetic rotor, then transfer the flask to a low-temperature reactor and start stirring. When the system temperature drops to the preset temperature of -18 ° C, slowly add titanium tetrachloride (6.5 mL) and let stand for 30 minutes. After the addition is complete, continue stirring for 30 minutes, then add zinc powder (7.8 g) in small portions several times within 30 minutes. Continue to stir the mixture at -18 ° C for 1 hour, then remove the low-temperature reactor and continue to react at room temperature for 3 hours.
[0069] Finally, the reaction was quenched by adding 100 mL of ice water, the solid was filtered and collected, and the solid was dissolved in 80 mL of dichloromethane and filtered twice to remove insoluble inorganic matter. The filtrate was evaporated and the residue was recrystallized with n-hexane to obtain compound B with a yield of 91.8%. GC-MS (m / z): calcd.for C 18 H 18 Br2S2,455.92,found 456.12.
[0070] Example 1
[0071] The preparation of the positive electrode precursor 1, the specific steps are as follows:
[0072] The positive electrode material is 8 series nickel cobalt manganese oxide (NCM811) 90.0, LATP (Li 1.4 Al 0.4 Ti 1.6 (PO4)3) 10.0g, put into a high-speed mixer, premix at 1000rpm for 20min, put the obtained premix into a fusion coating machine, and run at 2000rpm for 30min. Put the coated positive electrode material into a tubular furnace, and treat it at 100℃ for 2h under a nitrogen blanketing environment to obtain a positive electrode precursor 1 (the thickness of the shell layer of the first coating is between 200-400nm).
[0073] The preparation of intermediate 1, the specific steps are as follows:
[0074] Add cathode precursor 1 (19.1 g, 0.05 mol), compound A (42.8 g, 0.1 mol) and potassium carbonate (13.8 g, 0.1 mol) to DMF (1000 mL) solution at room temperature, start stirring, and then stir the mixture at 120 ° C for 24 h. After the reaction is completed, cool to room temperature, pour the reaction mixture into ice water (3000 mL), filter, and then wash three times with 300 mL of chloroform and ethanol respectively, and dry to obtain a modified cathode precursor 1, which is then added to alkaline conditions, stirred evenly for 30 min, filtered, and dried to obtain intermediate 1.
[0075] The preparation of the positive electrode composite 1 is carried out in the following specific steps:
[0076] 10.0 g of the intermediate 1 was taken and put into a fusion coating machine, which was operated at 2000 rpm for 30 min. The coated positive electrode material was put into a tubular furnace and treated at 200° C. for 3 h in a nitrogen-encapsulated environment to obtain a positive electrode composite 1.
[0077] The positive electrode composite 1 in Example 1 was subjected to SEM testing, and the results are shown in Figure 1 .
[0078] Figure 1 is a scanning electron microscope SEM image of the positive electrode composite 1, such as Figure 1 As shown, it can be clearly seen that the surface of the positive electrode composite 1 is coated with a dense coating layer, which is uniform and dense, and the size is at the micron level.
[0079] Prepare the electrolyte 1 sample, the specific steps are as follows:
[0080] In an argon glove box with a water and oxygen content of ≤0.1ppm, ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are uniformly mixed in a volume ratio of 10:15:65:10 to obtain an organic solvent, and then lithium hexafluorophosphate (LiPF6) and lithium difluorophosphate (LiPO2F2) are slowly added to the organic solvent. After complete dissolution, vinylene carbonate (VC), 1,3-propane sultone (PS), fluoroethylene carbonate (FEC), and vinyl sulfate (DTD) are added, and the electrolyte sample is obtained after stirring. Among them, the usage amounts of LiPF6, LiPO2F2, organic solvent, VC, PS, FEC, and DTD are 11%, 1%, 82.5%, 0.5%, 1.5%, 2.5%, and 1% of the total mass of the electrolyte, respectively.
[0081] Prepare the experimental battery 1 sample, the specific steps are as follows:
[0082] The positive electrode composite 1, conductive agent carbon black (Super P), conductive agent carbon nanotubes (CNT, NMP solution with a content of 4% by mass), and binder polyvinylidene fluoride (PVDF, NMP solution with a content of 5% by mass) were weighed and mixed according to a mass ratio of 97:1.2:0.8:1. After mixing, an appropriate amount of NMP was added to control the theoretical solid content to 65%. A planetary homogenizer was used to homogenize the positive electrode slurry, and the positive electrode slurry was evenly coated on both sides of a 17μm thick carbon-coated aluminum foil by transfer coating. After drying, rolling, and cutting, a positive electrode disc with a diameter of 12mm was obtained.
[0083] The negative electrode material artificial graphite, conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC, 1.5% by mass in deionized water solution), and binder styrene butadiene rubber (SBR, 48% by mass in deionized water solution) were mixed at a mass ratio of 95:1:1.5:2.5. After mixing, deionized water was added to control the theoretical solid content to 52%. A planetary homogenizer was used to homogenize the negative electrode slurry, and the negative electrode slurry was evenly coated on both sides of a 17μm thick carbon-coated copper foil by transfer coating. After drying, rolling, and cutting, a negative electrode disc with a diameter of 14mm was obtained. The N / P ratio of the positive and negative electrodes was 1.1.
[0084] A button cell was made in a glove box with a water and oxygen value of ≤0.1ppm. The negative electrode sheet, separator, positive electrode sheet, stainless steel gasket, and spring were stacked in order, 80μL of electrolyte was injected, and the battery was sealed using a hydraulic crimping machine. The battery was left to stand for 12h and aged to obtain experimental cell 1.
[0085] Example 2
[0086] The preparation of the positive electrode precursor 2, the specific steps are as follows:
[0087] 91.0 g of lithium nickel cobalt manganese oxide (811) and 9.0 g of LATP were placed in a high-speed mixer and premixed at 900 rpm for 25 min. The obtained premix was placed in a fusion coating machine and operated at 3000 rpm for 25 min. The coated positive electrode material was placed in a tubular furnace and treated at 100°C for 2 h in a nitrogen blanketing environment to obtain a positive electrode material precursor 2.
[0088] The preparation of intermediate 2, the specific steps are as follows:
[0089] At room temperature, positive electrode material precursor 2 (19.1 g, 0.05 mol), compound A (42.8 g, 0.1 mol) and sodium carbonate (10.6 g, 0.1 mol) were added to a DMF (1000 mL) solution, stirring was started, and the mixture was stirred at 120 ° C for 24 h. After the reaction was completed, it was cooled to room temperature, and the reaction mixture was poured into ice water (3000 mL), filtered, and then washed three times with 300 mL of chloroform and ethanol respectively, and dried to obtain a modified positive electrode precursor 2, which was then added to alkaline conditions, stirred evenly for 30 min, filtered, and dried to obtain intermediate 2.
[0090] The preparation of the positive electrode composite 2 is as follows:
[0091] 10.0 g of the intermediate 2 was taken and put into a fusion coating machine, which was operated at 2000 rpm for 30 min. The coated positive electrode material was put into a tubular furnace and treated at 250° C. for 3 h in a nitrogen-encapsulated environment to obtain a positive electrode composite 2.
[0092] The same operation as in Example 1 was followed to prepare the electrolyte 2 sample, except that the usage amounts of LiPF6, LiPO2F2, organic solvent, VC, PS and FEC were 12.5%, 1%, 83.5%, 0.5%, 0.5% and 2% of the total mass of the electrolyte, respectively.
[0093] The same operation as in Example 1 was followed to prepare an experimental battery 2, except that the positive electrode sheet prepared from the positive electrode composite 2 was used.
[0094] Example 3
[0095] The preparation of the positive electrode precursor 3, the specific steps are as follows:
[0096] 92.0 g of lithium nickel cobalt manganese oxide (811) and 8.0 g of LATP were placed in a high-speed mixer and premixed at 1800 rpm for 30 min. The obtained premix was placed in a fusion coating machine and operated at 3000 rpm for 25 min. The coated positive electrode material was placed in a tubular furnace and treated at 100°C for 2 h under a nitrogen blanketing environment to obtain a positive electrode precursor 3.
[0097] The preparation of intermediate 3, the specific steps are as follows:
[0098] Add cathode precursor 3 (19.1 g, 0.05 mol), compound A (42.8 g, 0.1 mol) and sodium carbonate (10.6 g, 0.1 mol) to DMF (1000 mL) solution at room temperature, start stirring, and then stir the mixture at 120 ° C for 24 h. After the reaction is completed, cool to room temperature, pour the reaction mixture into ice water (3000 mL), filter, and then wash three times with 300 mL of chloroform and ethanol respectively, and obtain the modified cathode precursor 3 after drying. Then add it to alkaline conditions, stir evenly for 30 min, filter and dry to obtain intermediate 3.
[0099] The preparation of the positive electrode composite 3, the specific steps are as follows:
[0100] 10.0 g of the intermediate 3 was taken and put into a fusion coating machine, which was operated at 2000 rpm for 30 min. The coated positive electrode material was put into a tubular furnace and treated at 200° C. for 3 h in a nitrogen-encapsulated environment to obtain a positive electrode composite 3.
[0101] The same operation as in Example 1 was followed to prepare electrolyte sample 3, except that the usage amounts of LiPF6, LiPO2F2, organic solvent, VC, PS and FEC were 11.5%, 0.5%, 85.5%, 1%, 0.5% and 1% of the total mass of the electrolyte, respectively.
[0102] The same operation as in Example 1 was followed to prepare an experimental battery 3, except that the positive electrode sheet prepared from the positive electrode composite 3 was used.
[0103] Example 4
[0104] The preparation of the positive electrode precursor 4, the specific steps are as follows:
[0105] 93.0 g of positive electrode lithium nickel cobalt manganese oxide (811) and 7.0 g of LATP were placed in a high-speed mixer and premixed at 2000 rpm for 30 min. The obtained premix was placed in a fusion coating machine and operated at 3000 rpm for 25 min. The coated positive electrode material was placed in a tubular furnace and treated at 100 ° C for 2 h under a nitrogen blanketing environment to obtain a positive electrode precursor 4.
[0106] The preparation of intermediate 4, the specific steps are as follows:
[0107] Add cathode precursor 4 (19.1 g, 0.05 mol), compound A (42.8 g, 0.1 mol) and sodium carbonate (10.6 g, 0.1 mol) to DMF (1000 mL) solution at room temperature, start stirring, and then stir the mixture at 120 ° C for 24 h. After the reaction is completed, cool to room temperature, pour the reaction mixture into ice water (3000 mL), filter, and then wash three times with 300 mL of chloroform and ethanol respectively, and obtain the modified cathode precursor 4 after drying. Then add it to alkaline conditions, stir evenly for 30 min, filter and dry to obtain intermediate 4.
[0108] The preparation of the positive electrode composite 4 is carried out in the following specific steps:
[0109] 10.0 g of the intermediate 4 was taken and put into a fusion coating machine, which was operated at 2500 rpm for 25 min. The coated positive electrode material was put into a tubular furnace and treated at 200° C. for 3 h in a nitrogen-encapsulated environment to obtain a positive electrode composite 4.
[0110] The same operation as in Example 1 was followed to prepare electrolyte sample 4, except that the usage amounts of LiPF6, LiPO2F2, organic solvent, VC, PS and FEC were 12%, 1%, 84%, 1%, 0.5% and 1.5% of the total mass of the electrolyte, respectively.
[0111] The same operation as in Example 1 was followed to prepare an experimental battery 4, except that a positive electrode sheet prepared from the positive electrode composite 4 was used.
[0112] Example 5
[0113] The preparation of the positive electrode precursor 5, the specific steps are as follows:
[0114] 94.0 g of positive electrode lithium nickel cobalt manganese oxide (811) and 6.0 g of LATP were placed in a high-speed mixer and premixed at 2000 rpm for 30 min. The obtained premix was placed in a fusion coating machine and operated at 3000 rpm for 25 min. The coated positive electrode material was placed in a tubular furnace and treated at 100 ° C for 2 h under a nitrogen blanketing environment to obtain a positive electrode precursor 5.
[0115] The preparation of intermediate 5, the specific steps are as follows:
[0116] At room temperature, positive electrode precursor 5 (19.1 g, 0.05 mol), compound A (42.8 g, 0.1 mol) and sodium carbonate (10.6 g, 0.1 mol) were added to a DMF (1000 mL) solution, and stirring was started. The mixture was then stirred at 120 ° C for 24 h. After the reaction was completed, it was cooled to room temperature, and the reaction mixture was poured into ice water (3000 mL), filtered, and then washed three times with 300 mL of chloroform and ethanol respectively, and dried to obtain a modified positive electrode precursor 5, which was then added to alkaline conditions, stirred evenly for 30 min, and filtered and dried to obtain intermediate 5.
[0117] The preparation of the positive electrode composite 5 is carried out in the following specific steps:
[0118] 10.0 g of the intermediate 5 was taken and put into a fusion coating machine, which was operated at 2800 rpm for 25 min. The coated positive electrode material was put into a tubular furnace and treated at 300° C. for 2 h in a nitrogen-encapsulated environment to obtain a positive electrode composite 5.
[0119] The same operation as in Example 1 was followed to prepare electrolyte sample 5, except that the amounts of LiPF6, LiPO2F2, organic solvent, VC, PS and FEC used were 13.5%, 1%, 82.5%, 1%, 1% and 1% of the total mass of the electrolyte, respectively.
[0120] The same operation as in Example 1 was followed to prepare an experimental battery 5, except that a different compound was used, and a positive electrode sheet prepared from the positive electrode composite 5 was used.
[0121] Example 6
[0122] The preparation of the positive electrode precursor 6, the specific steps are as follows:
[0123] 95.0 g of positive electrode lithium nickel cobalt manganese oxide (811) and 5.0 g of LATP were placed in a high-speed mixer and premixed at 2000 rpm for 30 min. The obtained premix was placed in a fusion coating machine and operated at 3000 rpm for 25 min. The coated positive electrode material was placed in a tubular furnace and treated at 100 ° C for 2.5 h under a nitrogen blanketing environment to obtain a positive electrode precursor 6.
[0124] The preparation of intermediate 6, the specific steps are as follows:
[0125] Add cathode material precursor 6 (19.1 g, 0.05 mol), compound A (42.8 g, 0.1 mol) and sodium carbonate (10.6 g, 0.1 mol) to DMF (1000 mL) solution at room temperature, start stirring, and then stir the mixture at 120 ° C for 24 h. After the reaction is completed, cool to room temperature, pour the reaction mixture into ice water (3000 mL), filter and wash three times with 300 mL of chloroform and ethanol respectively, and obtain the modified cathode precursor 6 after drying. Then add it to alkaline conditions, stir evenly for 30 minutes, filter and dry to obtain intermediate 6.
[0126] The preparation of the positive electrode composite 6 is carried out in the following specific steps:
[0127] 10.0 g of the intermediate 6 was taken and put into a fusion coating machine, which was operated at 2500 rpm for 25 min. The coated positive electrode material was put into a tubular furnace and treated at 300° C. for 2 h in a nitrogen-encapsulated environment to obtain a positive electrode composite 6.
[0128] The same operation as in Example 1 was followed to prepare the electrolyte sample 1. This example uses the electrolyte sample 1.
[0129] The same operation as in Example 1 was followed to prepare an experimental battery 6, except that a different compound was used, and a positive electrode sheet prepared from the positive electrode composite 6 was used.
[0130] Example 7
[0131] The preparation of the positive electrode precursor 7, the specific steps are as follows:
[0132] 96.0 g of positive electrode lithium nickel cobalt manganese oxide (811) and 4.0 g of LATP were placed in a high-speed mixer and premixed at 2000 rpm for 30 min. The obtained premix was placed in a fusion coating machine and operated at 3000 rpm for 30 min. The coated positive electrode material was placed in a tubular furnace and treated at 100 ° C for 2 h under a nitrogen blanket environment to obtain a positive electrode precursor 7.
[0133] The preparation of intermediate 7, the specific steps are as follows:
[0134] Add cathode precursor 7 (19.1 g, 0.05 mol), compound A (42.8 g, 0.1 mol) and sodium carbonate (10.6 g, 0.1 mol) to DMF (1000 mL) solution at room temperature, start stirring, and then stir the mixture at 120 ° C for 24 h. After the reaction is completed, cool to room temperature, pour the reaction mixture into ice water (3000 mL), filter, and then wash three times with 300 mL of chloroform and ethanol respectively, and obtain the modified cathode precursor 7 after drying. Then add it to alkaline conditions, stir evenly for 30 minutes, filter and dry to obtain intermediate 7.
[0135] The preparation of the positive electrode composite 7 is carried out in the following specific steps:
[0136] 10.0 g of the intermediate 7 was taken and put into a fusion coating machine, which was operated at 2500 rpm for 30 min. The coated positive electrode material was put into a tubular furnace and treated at 300° C. for 2 h in a nitrogen-encapsulated environment to obtain a positive electrode composite 7.
[0137] The same operation as in Example 1 was followed to prepare electrolyte sample 2. This example uses electrolyte sample 2.
[0138] The same operation as in Example 1 was followed to prepare an experimental battery 7, except that a different compound was used, and a positive electrode sheet prepared from the positive electrode composite 7 was used.
[0139] Example 8
[0140] The preparation of the positive electrode precursor 8, the specific steps are as follows:
[0141] 97.0 g of positive electrode lithium nickel cobalt manganese oxide (811) and 3.0 g of LATP were placed in a high-speed mixer and premixed at 2000 rpm for 30 min. The obtained premix was placed in a fusion coating machine and operated at 3000 rpm for 20 min. The coated positive electrode material was placed in a tubular furnace and treated at 100 ° C for 2 h under a nitrogen blanket environment to obtain a positive electrode precursor 8.
[0142] The preparation of intermediate 8, the specific steps are as follows:
[0143] Add cathode material precursor 8 (19.1 g, 0.05 mol), compound A (42.8 g, 0.1 mol) and sodium carbonate (10.6 g, 0.1 mol) to DMF (1000 mL) solution at room temperature, start stirring, and then stir the mixture at 120 ° C for 24 h. After the reaction is completed, cool to room temperature, pour the reaction mixture into ice water (3000 mL), filter, and then wash three times with 300 mL of chloroform and ethanol respectively, and obtain the modified cathode precursor 8 after drying. Then add it to alkaline conditions, stir evenly for 30 minutes, filter and dry to obtain intermediate 8.
[0144] The preparation of the positive electrode composite 8 is carried out in the following specific steps:
[0145] 10.0 g of the intermediate 8 was taken and put into a fusion coating machine, which was operated at 2500 rpm for 30 min. The coated positive electrode material was put into a tubular furnace and treated at 250° C. for 2 h in a nitrogen-encapsulated environment to obtain a positive electrode composite 8.
[0146] The same operation as in Example 1 was followed to prepare electrolyte sample 3, and this example used electrolyte sample 3.
[0147] The same operation as in Example 1 was followed to prepare an experimental battery 8, except that a different compound was used, and a positive electrode sheet prepared from the positive electrode composite 8 was used.
[0148] Example 9
[0149] The preparation of the positive electrode precursor 9, the specific steps are as follows:
[0150] 98.0 g of positive electrode lithium nickel cobalt manganese oxide (811) and 2.0 g of LATP were placed in a high-speed mixer and premixed at 2500 rpm for 25 min. The obtained premix was placed in a fusion coating machine and operated at 2500 rpm for 25 min. The coated positive electrode material was placed in a tubular furnace and treated at 100 ° C for 2 h under a nitrogen blanketing environment to obtain a positive electrode precursor 9.
[0151] The preparation of intermediate 9, the specific steps are as follows:
[0152] Add cathode precursor 9 (19.1 g, 0.05 mol), compound A (42.8 g, 0.1 mol) and sodium carbonate (10.6 g, 0.1 mol) to DMF (1000 mL) solution at room temperature, start stirring, and then stir the mixture at 120 ° C for 24 h. After the reaction is completed, cool to room temperature, pour the reaction mixture into ice water (3000 mL), filter, and then wash three times with 300 mL of chloroform and ethanol respectively, and obtain the modified cathode precursor 9 after drying. Then add it to alkaline conditions, stir evenly for 30 minutes, filter and dry to obtain intermediate 9.
[0153] The preparation of the positive electrode composite 9 is carried out in the following specific steps:
[0154] 10.0 g of the intermediate 9 was taken and put into a fusion coating machine, which was operated at 2500 rpm for 30 min. The coated positive electrode material was put into a tubular furnace and treated at 250° C. for 3 h in a nitrogen-encapsulated environment to obtain a positive electrode composite 9.
[0155] The same operation as in Example 1 was followed to prepare electrolyte sample 4, and this example used electrolyte sample 4.
[0156] The same operation as in Example 1 was followed to prepare an experimental battery 9, except that a different compound was used, and a positive electrode sheet prepared from the positive electrode composite 9 was used.
[0157] Example 10
[0158] The preparation of the positive electrode precursor 10 includes the following specific steps:
[0159] 99.0 g of positive electrode lithium nickel cobalt manganese oxide (811) and 1.0 g of LATP were placed in a high-speed mixer and premixed at 2500 rpm for 30 min. The obtained premix was placed in a fusion coating machine and operated at 2500 rpm for 25 min. The coated positive electrode material was placed in a tubular furnace and treated at 100°C for 2 h in a nitrogen blanketing environment to obtain a positive electrode precursor 10.
[0160] The preparation of intermediate 10 is as follows:
[0161] Add cathode precursor 10 (19.1 g, 0.05 mol), compound B (45.6 g, 0.1 mol) and sodium carbonate (10.6 g, 0.1 mol) to DMF (1000 mL) solution at room temperature, start stirring, and then stir the mixture at 120 ° C for 24 h. After the reaction is completed, cool to room temperature, pour the reaction mixture into ice water (3000 mL), filter, and then wash three times with 300 mL of chloroform and ethanol respectively, and obtain the modified cathode precursor 10 after drying. Then add it to alkaline conditions, stir evenly for 30 minutes, filter and dry to obtain intermediate 10.
[0162] The preparation of the positive electrode composite 10 is carried out in the following specific steps:
[0163] 10 g of the intermediate 10 was taken and put into a fusion coating machine, which was operated at 3000 rpm for 30 min. The coated positive electrode material was put into a tubular furnace and treated at 300° C. for 2 h in a nitrogen-encapsulated environment to obtain a positive electrode composite 10.
[0164] The same operation as in Example 1 was followed to prepare electrolyte sample 5. This example uses electrolyte sample 5.
[0165] The same operation as in Example 1 was followed to prepare an experimental battery 10 , except that a different compound was used, and a positive electrode sheet prepared from the positive electrode composite 10 was used.
[0166] Comparative Example 1
[0167] The same operation as in Example 1 was followed to prepare a sample of electrolyte 1, and this comparative example used the sample of electrolyte 1.
[0168] The experimental battery 11 was prepared by the same operation as in Example 1, except that the positive electrode material used was uncoated lithium nickel cobalt manganese oxide (811).
[0169] Comparative Example 2
[0170] The same operation as in Example 1 was followed to prepare a sample of electrolyte 1, and this comparative example used the sample of electrolyte 1.
[0171] The experimental battery 12 was prepared by the same operation as in Example 1, except that the positive electrode material used was a once-coated lithium nickel cobalt manganese oxide precursor (811).
[0172] Comparative Example 3
[0173] The same operation as in Example 1 was followed to prepare a sample of electrolyte 1, and this comparative example used the sample of electrolyte 1.
[0174] The experimental battery 13 was prepared by the same operation as in Example 1, except that the positive electrode material used was a mixture of a primary coated lithium nickel cobalt manganese oxide precursor (811) and compound A.
[0175] The lithium ion batteries prepared in Examples 1 to 10 and Comparative Examples 1 to 3 were subjected to cycle performance tests and electrochemical tests, and the test contents are as follows:
[0176] Specific capacity test:
[0177] The prepared lithium-ion battery was placed in a constant temperature room at an ambient temperature of 25°C and a current of 0.1C for the first charge and discharge curve test. Figure 2 Capacity-voltage curves of Example 1 and Comparative Example 1.
[0178] Battery room temperature cycle test
[0179] The prepared lithium-ion battery was placed in a constant temperature room with an ambient temperature of 25°C, with a current of 1C and a voltage of 4.2V, and constant current and constant voltage charging to a cut-off current of 0.05C, and then discharged at a constant current of 1C to a voltage of 3V (b is determined according to the positive electrode material), and cycled for 100 cycles. The capacity retention rate was recorded, and the nth cycle capacity retention rate (%) = (nth cycle discharge specific capacity / first cycle discharge specific capacity) * 100%.
[0180] Battery high temperature cycle test
[0181] The prepared lithium-ion battery was placed in a constant temperature box at a temperature of 45°C or 60°C, with a current of 1C and a voltage of 4.2V, and constant current and constant voltage charging until the cut-off current was 0.05C, and then discharged at a constant current of 1C to a voltage of 3V, and cycled for 80 or 50 weeks, and the capacity retention rate was recorded. The capacity retention rate of the nth cycle (%) = (discharge specific capacity of the nth cycle / discharge specific capacity of the first cycle) * 100%.
[0182] Battery rate discharge test
[0183] The prepared lithium-ion battery was placed in a constant temperature room at an ambient temperature of 25°C, with a current of 1C and a voltage of 4.2V, and constant current and constant voltage charging to a cut-off current of 0.05C. It was then discharged at constant currents of 0.2C / 0.5C / 1C / 2C / 3 / C / 0.2C to a voltage of 3V, and the capacity retention rate was recorded. Capacity retention rate at different rates (%) = (discharge specific capacity at different rates / discharge specific capacity at 0.2C) * 100%.
[0184] Figure 2 The first charge and discharge curves of Example 1 and Comparative Example 1 at 0.1C. At a charge and discharge current density of 0.1C, the first discharge capacity of Example 1 is 206.0 mAh·g -1 The first coulombic efficiency is as high as 91.38%; the first discharge capacity of comparative example 1 is 204 mAh g -1 The first coulombic efficiency was as high as 89.12%, indicating that this composite coating can improve the electrochemical performance of the positive electrode material.
[0185] The positive electrode active materials in Examples 1 to 10 and Comparative Examples 1 to 3 were used to prepare solid-liquid hybrid lithium batteries. The battery performance test results are shown in Table 1.
[0186] Table 1. Performance test results of lithium ion batteries prepared in Examples 1 to 10 and Comparative Examples 1 to 3
[0187]
[0188] As can be seen from Table 1, the positive electrode composites prepared in Examples 1 to 10 are used in solid-liquid hybrid lithium batteries, and at different cycle test temperatures, they all show better capacity retention rates than those of Comparative Examples 1 to 3, proving that the present invention has a significant improvement in the electrical performance of lithium batteries by using solid electrolyte composites to coat the positive electrode materials.
[0189] It is particularly noteworthy that, compared with Example 1, the untreated lithium nickel cobalt manganese oxide (811) used in Comparative Example 1 has a cycle performance far lower than that of Example 1, while Comparative Example 2 is a lithium nickel cobalt manganese oxide precursor that has only been coated with a solid electrolyte once. Compared with Comparative Example 1, although the room temperature cycle performance is improved, the high temperature (45-60°C) cycle performance is still poor; Comparative Example 3 adds compound A on the basis of Comparative Example 2, but the high temperature cycle performance is less improved and the effect is not significant.
[0190] The above test results can be attributed to the fact that the present invention ingeniously coats the oxide solid electrolyte on the positive electrode material to form a core-shell-shell double-layer coating structure, which can directly isolate the contact between the positive electrode material and the electrolyte, and effectively prevent the side reactions of the two. At the same time, the present invention innovatively introduces a functional compound formula I structure to modify the solid electrolyte on the coating layer, converting the residual alkali in the solid electrolyte into a favorable component, blocking the high-temperature side reaction of the solid electrolyte and the solvent from the source, alleviating the side reaction of the electrolyte and the positive electrode as a whole, inhibiting the dissolution of transition metal elements, and thereby improving the high-temperature cycle performance of the lithium battery.
[0191] The solid-liquid hybrid lithium battery was prepared by using Example 1 and Comparative Example 1. The rate discharge performance test results are as follows: Figure 3 As shown, it can be seen that the solid-liquid hybrid lithium battery prepared in Example 1 shows a better capacity retention rate than that of Comparative Example 1, proving that the nickel cobalt manganese oxide lithium positive electrode material of the present invention, which is composite-coated with an oxide solid electrolyte, has a significant effect on improving the rate discharge performance of the nickel cobalt manganese oxide lithium battery. This test result is mainly due to the presence of an oxide solid electrolyte layer and an outermost coating layer in the modified positive electrode composite of the double-layer coating structure obtained by the composite coating method, which can form a conductive network during the battery charging and discharging process, improve the electron conduction capacity, and cooperate with the inherent fast ion conduction capacity of the oxide solid electrolyte, which can take into account the improvement of both electronic conductivity and ion conductivity, thereby significantly alleviating the polarization phenomenon after rapid charging and discharging, so as to achieve the purpose of enhancing the battery rate capacity.
[0192] The present invention adopts a composite coating method, completes primary coating of a positive electrode material and a solid electrolyte by physical mixing and high-temperature sintering, and then modifies the solid electrolyte by synthesizing a functional compound, so that compound A can be grafted onto the positive electrode material containing a solid electrolyte coating layer on the surface, and forms another dense polymer coating layer outside the solid electrolyte coating layer by utilizing the reaction of compound A with residual alkali and the polymerizable groups contained therein, and finally completes secondary coating by heat treating the polymer coating layer, and finally forms a positive electrode composite with a double-layer core-shell-shell structure and a stable structure, which has higher electronic conductivity and ion conductivity, can give a fast charge transmission capability between the interface and the bulk phase, and simultaneously blocks the side reaction between the positive electrode material and the electrolyte, and the solid electrolyte and the solvent, and finally uses a solid-liquid hybrid lithium ion battery prepared by using the positive electrode composite to show more excellent electrochemical performance and better safety performance.
[0193] At the same time, the synthesis method and route of the thiophene compound represented by Formula I of the present invention are relatively simple, the raw materials are easily available, the cost is low, and the rate and high-temperature cycle performance can be solved simultaneously, which is a very cost-effective method.
[0194] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A thiophene compound, characterized in that: Having the structure of formula I: Wherein, X1 and X2 are independently selected from halogen elements.
2. A modified positive electrode material, characterized in that: From the inside to the outside, it includes a lithium-containing core, a solid electrolyte shell layer coated on the surface of the lithium-containing core, and a carbon-containing shell layer. The carbon-containing shell layer is formed by carbonization after polymerization of a monomer, and the monomer is the thiophene compound according to claim 1.
3. The modified positive electrode material according to claim 2, characterized in that: The composition of the lithium-containing core is selected from one or more of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel manganese oxide and lithium-rich lithium manganese oxide.
4. The modified positive electrode material according to claim 2, characterized in that The solid electrolyte shell layer is composed of a NASICON type oxide solid electrolyte.
5. A method for preparing a modified positive electrode material, characterized in that: The following steps are involved: Providing a lithium-containing positive electrode material coated with a solid electrolyte shell layer; The lithium-containing positive electrode material coated with the solid electrolyte shell layer is reacted with a functional compound, wherein the functional compound is the thiophene compound according to claim 1, so that the thiophene compound is grafted onto the surface of the solid electrolyte shell layer and polymerized into a coating film to obtain an intermediate; The intermediate is subjected to pyrolysis treatment under a protective atmosphere to obtain a modified positive electrode material with a double-layer coating structure.
6. The preparation method according to claim 5, characterized in that: In the lithium-containing positive electrode material coated with a solid electrolyte shell layer, the thickness of the solid electrolyte shell layer is 200 to 400 nm; The preparation of the lithium-containing positive electrode material coated with a solid electrolyte shell layer comprises: dry-mixing the lithium-containing positive electrode material raw material and the solid electrolyte, and sintering them at 90-300° C. to obtain the obtained material.
7. The preparation method according to claim 6, characterized in that: During the preparation process of the lithium-containing positive electrode material coated with the solid electrolyte shell layer, the mass ratio of the lithium-containing positive electrode material raw material to the solid electrolyte is (1-m): m, 0<m≤0.1; the composition of the solid electrolyte shell layer is NASICON type oxide solid electrolyte; the temperature of the high-temperature sintering is 0.2 to 0.5 times the melting point of the solid electrolyte.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The reaction between the lithium-containing positive electrode material coated with a solid electrolyte shell layer and the functional compound is carried out by stirring in the presence of an alkaline solution; the molar ratio of the lithium-containing positive electrode material and the functional compound is (0.4-0.6):1; the alkaline solution is a carbonate aqueous solution with a molar concentration of 0.1-0.2 mol / L, the reaction temperature is 100-120°C, and the reaction time is 24-30 hours.
9. The preparation method according to claim 8, characterized in that: The temperature of the pyrolysis treatment is 200-300° C., and the time is 20-30 minutes.
10. A positive electrode sheet, characterized in that: The modified positive electrode material according to any one of claims 2 to 4, or the modified positive electrode material obtained by the preparation method according to any one of claims 5 to 9 is used as the active material.
11. A lithium ion battery, characterized in that: Including the positive electrode sheet as claimed in claim 10.
Citation Information
Patent Citations
Positive electrode material directly coated with solid electrolyte and technological method thereof
CN108682819A
Electrolyte containing silicon solvent and thiophene additives and lithium ion battery using the same
CN109786830A
Electrolyte containing thiophene additive and lithium ion battery using electrolyte
CN116799306A
Process for the electrochemical preparation, with the addition of Brönsted acids, of electroconductive poly(alkoxythiophenes)
EP0416570A2
Organic thin film, and photoelectric conversion element using the same
JP2014034618A